Islamic education and Zaid bin Harethah Model - Al- Yazidi, Sabah Saqr Ghammid (Journal of Educational and Psychological Sciences, 2019)
The study aims to identify the education of the prophet Muhammad (peace be upon him) for Muslim child. It also aims to show how the Prophet act with Zaid educationally. The researcher used the analytical descriptive method in describing and analyzing the Prophet's (peace be upon him) method of dealing with the Muslim child. In addition to the methods the Prophet (peace be upon him) acting through the Al- hadeeth, and their educational applications. The study consisted of three chapters and a conclusion, where the first chapter includes the research plan, while second chapter includes the concept of education in the Sunnah. The researcher explained, in the third chapter, methods of Islamic education. In addition, Chapter four includes an analytical study of Zaid's story, while Chapter five includes the findings and recommendations, then the conclusion.
Keywords: Zaid bin Haritha; Islam; Education; the Prophet's Sunnah